Keterwakilan Politik Anggota Perempuan dalam Badan Permusyawaratan Desa Sanur Kauh Periode 2013 – 2019 - Jaya Prawira, I Nyoman Adi; -, Bandiyah; Ali Azhar, Muhammad (Jurnal Nawala Politika, 2021)
This study aims to answer the formulation of the problem, namely how is the political representation of women members in the Village Consultative Body in Sanur Kauh Village for the period 2013 - 2019. This study uses Political Presence Theory and Representation Theory. The research method used is a qualitative method. The results of this study indicate that first the Political Presence of BPD Women Members has been fulfilled descriptively. Both are substantively fulfilled but there are obstacles where not all aspirations are realized. Third, personal transformation has not been fulfilled where BPD Perempuan members have not made significant changes to women in Sanur Kauh Village, but are able to make changes personally. Fourth, formal, symbolic and substantive representations have been fulfilled, while descriptive representations have not been fulfilled because female BPD members have not been able to represent all female characters in Sanur Kauh Village. Keyword: Women's Political Representation, Village Consultative Body, Sanur Kauh Village.